Disrupción de vía biliar en colecistectomía abierta vs laparoscópica en el Hospital General Regional No.1 IMSS, Morelia Michoacán, 2022 - Sánchez Neri, Andrea (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
INTRODUCTION: Cholelithiasis is one of the main surgical pathologies in Mexico and one of the most performed surgeries. Bile duct disruption is a complication that is difficult to diagnose and treat, and prevention is a priority. OBJECTIVE: To determine the prevalence of disruptions and associated factors in cholecystectomies at the Regional General Hospital No. 1, Michoacán, during 2022. METHODS: Retrospective, observational cross-sectional study of 667 beneficiaries of the HGR1 IMSS Morelia during 2022, over 18 years of age undergoing cholecystectomy, with bile duct disruption. A database was made with identified cases, variables studied, and the results are presented in frequencies, percentages, measures of dispersion and association of variables. RESULTS: The prevalence of disruptions was 4.8%, laparoscopic was 1.1%, open 9.6%. The most frequent type of disruption was Strasberg A, 85.7% in open surgeries. The mean age was 45 years and cholecystectomies were mainly performed in women. The most associated comorbid was arterial hypertension. The presence of gallbladder exacerbation, emergency surgery, partial cholecystectomy, Parkland and Doublet scale score of 4 and 4-6 points in laparoscopic surgeries, as well as thickened cystic, non-visible cystic artery, inflamed walls and Mirizzi syndrome showed a statistically significant difference for the presence of disruption. CONCLUSION: The prevalence of disruptions in the Hospital General Regional No. 1 was higher than that found in the literature, with 66 times greater probability of presenting with open cholecystectomy than with laparoscopic cholecystectomy.

INTRODUCCIÓN: La colelitiasis es una de las principales patologías quirúrgicas en México y de las cirugías más realizadas. La disrupción de vía biliar es una complicación con difícil diagnóstico y tratamiento, siendo prioritaria su prevención. OBJETIVO: Determinar la prevalencia de disrupciones y factores asociados en Colecistectomías en el Hospital General Regional No 1, Michoacán, durante el 2022. MÉTODOS: Estudio Transversal, observacional retrospectivo de 667 derechohabientes del HGR1 IMSS Morelia durante el 2022, mayores de 18 años sometidos a Colecistectomía, con disrupción de vía biliar. Se realizó una base de datos con casos identificados, variables estudiadas y se presentan los resultados en frecuencias, porcentajes, medidas de dispersión y asociación de variables. RESULTADOS: La prevalencia de disrupciones fue de 4.8%, por vía laparoscópica fue de 1.1%, abierta 9.6%. El tipo de disrupción más frecuente fue Strasberg A, 85.7% en cirugías abiertas. La edad media fue de 45 años y principalmente se realizaron colecistectomías en mujeres. El comórbido más asociado fue Hipertensión arterial. La presencia de agudización vesicular, cirugía de urgencia, colecistectomía parcial, puntaje de 4 en escala de Parkland y Doublet de 4-6 puntos en cirugías laparoscópicas, así como cístico engrosado, arteria cística no visible, paredes inflamadas y síndrome de Mirizzi mostraron una diferencia estadísticamente significante para la presencia de disrupción. CONCLUSIÓN: La prevalencia de disrupciones en el Hospital General Regional No. 1 fue mayor al encontrado en la bibliografía, con 66 veces mayor probabilidad de presentarse ante Colecistectomía abierta que laparoscópica.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Cirugía General
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19105; info:eu-repo/classification/cti/3; FCMB-E-2025-0145; Disrupción de la vía biliar; Colecistectomía; Ictericia